ANALYSIS OF KIDNEY FAILURE RISK FACTORS AMONG HYPERTENSIVE PATIENTS IN BAROS SERANG BANTEN - Fiora Ladesvita; Diah Tika Anggraeni; Florensia Lima (Jurnal Kesehatan Medika Saintika, 2020)
Hypertension is one of predisposing factors for decreased kidney function. Early detection of the risk of kidney failure is important to prevent further damage of kidneys because of hypertension. The purpose of this study was to analyze risk factors for kidney failure in hypertensive patients in Baros, Serang, Banten. The research method used was a quantitative study with a cross sectional design and a total sampling technique with  total sample size was 46 people according to the inclusion criteria. The instruments used were a stress level questionnaire and an observation sheet to record blood pressure, proteinuria, albuminuria, and urine creatinine as measured by the Rapid Test Complete Urine Test Strips. The results showed, as many as 22 people (47.8%) with a salt consumption pattern of more than 1 teaspoon a day, 14 people (30.4%) with a history of hypertension in the family and 16 people (34.8%) with mild stress levels, were at risk for chronic renal failure (OR 4.25; p value = 0.019; OR 4.71; p value = 0.029; p value = 0.012). In addition, there was a significant relationship between systolic blood pressure, albuminuria, proteinuria, and urine creatinine with the albumin creatinine ratio (p value 0.000; 0.001; 0.018; 0,001). It is concluded that of the 11 factors, there are 7 factors that are associated with the risk of chronic renal failure in hypertensive patients based on the albumin creatinine ratio.